Efecto de tres dosis de un Trihormonal en el cuajado de persea americana mill. var. Hass en Pacasmayo - La Libertad - Rodríguez Núñez, Franklyn Eduardo (2017)
The present investigation was carried out during the months of June 2017 - October 2017, in Santa Rosa, located in the district of San Jose, province of Pacasmayo, La Libertad Region. Geographically located at a latitude 7°21'20.24"S and to a length of 79°24'55.69"O. Currently the province of Pacasmayo and around has a temperature ranging between 20°C to 26 ºC. Our goal in the investigation was to evaluate the effect of three doses of a trihormonal applied to favor the curdling of Persea americana Mill. Var. Hass in Pacasmayo – La Libertad. The Randomized complete block desig with four treatments including the witness and three replications: Without application (T0), 0.30 l. cil-1 (T1), 0.35 l. cil-1 (T2), and 0.40 l. cil-1 (T3), respectively. Analysis was carried out of 95% of the variance for the data generated by the assessments and the significance test of Tukey Test How to test multiple comparison of means with a grade of 0.05% of significance. The results obtained indicate that the variable (filled with fruits) presents statistical significant difference; in which the treatment (T3) was the best of the treatments, obtaining the highest percentage of curdled 0.0349%.